(untitled) (Economic and Political Thought, 2017)
Within the work on the development of the post-Keynesian theory in the contemporary economics, attempts made by English classical economists are continued. The main aim is to explain the issues of economic growth, capital accumulation and technical progress as well as income distribution. The theory explains the reasons for divergent development observed in the North and the South of Europe and constitutes grounds for critical assessment of the European liberalisation and deregulation as well as the adopted hierarchy of objectives and limits imposed. There are no theoretical reasons for the convergence criteria in which there is no employment level, but there is a priority of inflation, a budget deficit and public debt limit (and a principle of the central bank independence). These have contributed to the aggravation of the effects of the crisis, especially in the countries of Southern Europe.